Pengaruh Kepatuhan Wajib Pajak, Efektifitas Sistem, Perpajakan dan Pendapatan Terhadap Penerimaan Pajak Kendaraan Bermotor (Studi Kasus Di Kota Palangka Raya) - Supriyadi; Yanson I Nyalung; Abdul Djalil (FKIP, Universitas Palangka Raya, 2020)
The low participation rate taxpayer in paying taxes, the tax system ineffective and inefficient as well as lower income tax payers who cause reception MVT does not match the set target. The aim of the study to determine the effect of Taxpayer Compliance, Tax and Revenue System Effectiveness against MVT Acceptance either partially or simultaneously. Research method with approach according to sample accidential sampling technique and quantitative descriptive research type. By distributing questionnaires to taxpayers, this research was conducted at SAMSAT Office of Palangka Raya. The observed variables include (1) Taxpayer Compliance, (2) Effectiveness of Taxation System, (3) Income and (4) Acceptance of MVT. Results showed partial Taxpayer Compliance positive and significant effect on the MVT Acceptance namely tcount 3.574 > ttable 1.960, while for the Taxation System Effectiveness and no significant negative effect on the acceptance of MVT is tcount -1.264 < ttable 1.960 and income and no significant positive effect on the MVT acceptance is tcount 0.284 < ttabel 1.960. Simultaneously the Taxpayer Compliance, Tax and Revenue System Effectiveness positive and significant impact on the Acceptance Agreement with tcount 4.716 > 1.960 ttabel.